2022
DOI: 10.51327/uqmh2278
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leader Motivating Language on Workplace Spirituality

Abstract: This article aims to study the influence of leader motivating language on three elements of workplace spirituality. It is hypothesized that leader motivational speech will be positively related to inner life, sense of community, and meaningful work. Data from 337 individuals from the US was collected using Amazon Mechanical Turk. Results from partial least squares indicate that leader motivating language is positive and significantly related to the three elements of workplace spirituality. Leader motivating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The quest of individuals to draw strength for peaceful IL by acting ethically and doing good to others is supported by ethical climate (Crowley, 2021). Under an ethical climate, a mechanism is formulated through peer and superior support, organizational values and the overall mindset prevailing in the organization, which provides opportunity to individuals to enhance virtuous aspect of their personalities that strengthens their inner lives in an organizational climate where ethical behavior is not emphasized (Daniel et al, 2022). Resultantly, the expected impact of ethical climate on inner lives of employees in an organization is anticipated to be positive and it is hypothesized that.…”
Section: Ethical Climate Vs Inner Lifementioning
confidence: 99%
See 3 more Smart Citations
“…The quest of individuals to draw strength for peaceful IL by acting ethically and doing good to others is supported by ethical climate (Crowley, 2021). Under an ethical climate, a mechanism is formulated through peer and superior support, organizational values and the overall mindset prevailing in the organization, which provides opportunity to individuals to enhance virtuous aspect of their personalities that strengthens their inner lives in an organizational climate where ethical behavior is not emphasized (Daniel et al, 2022). Resultantly, the expected impact of ethical climate on inner lives of employees in an organization is anticipated to be positive and it is hypothesized that.…”
Section: Ethical Climate Vs Inner Lifementioning
confidence: 99%
“…In topdown direction the leaders take care of their sub-ordinates and try to make their leadership successful and memorable. They adds to their LS and at the same time enhance the peace in their IL (minimizing regret, grief, helplessness and affective deficiency) (Daniel et al, 2022). In bottomup direction the followers do their best to achieve the objectives set by their leaders which adds to LS in the form of individual and group achievements.…”
Section: Inner Life Vs Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pio and Lengkong (2020) reported that spirituality at work positively influences ethical behavior among leaders. Daniel et al (2022) reported that leader motivating language was positively related to WPS.…”
Section: Leadershipmentioning
confidence: 99%